2017
DOI: 10.1002/acm2.12199
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric effects of anatomical changes during fractionated photon radiation therapy in pancreatic cancer patients

Abstract: Pancreatic tumors show large interfractional position variation. In addition, changes in gastrointestinal gas volumes and body contour take place over the course of radiation therapy. We aimed to quantify the effect of these anatomical changes on target dose coverage, for the clinically used fiducial marker‐based patient position verification and, for comparison, also for simulated bony anatomy‐based position verification. Nine consecutive patients were included in this retrospective study. To enable fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 25 publications
(36 reference statements)
5
16
0
Order By: Relevance
“…With respect to the setup correction method, it has been suggested that marker-matching and OM are far superior to skin-markingmatching methods and superior even to BM in photon therapy. 10 Likewise, in carbon ion therapy (CIRT), OM and marker-matching are reportedly superior to BM for the lung and liver. 11,12 Meanwhile, in CIRT for pancreatic cancer, a small effect of the setup correction method on dose distribution was demonstrated 13 ; this is because the dose distribution in particle therapy, compared with photon therapy, is easily distorted by interfractional anatomical variations such as changes in physique and gastrointestinal gas in abdominal therapy.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the setup correction method, it has been suggested that marker-matching and OM are far superior to skin-markingmatching methods and superior even to BM in photon therapy. 10 Likewise, in carbon ion therapy (CIRT), OM and marker-matching are reportedly superior to BM for the lung and liver. 11,12 Meanwhile, in CIRT for pancreatic cancer, a small effect of the setup correction method on dose distribution was demonstrated 13 ; this is because the dose distribution in particle therapy, compared with photon therapy, is easily distorted by interfractional anatomical variations such as changes in physique and gastrointestinal gas in abdominal therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Weight changes during RT are often seen and also cause the body contour to change. There are very few studies on the dosimetric effect that may occur due to the change of the body contour [29,30]. In this study, it is observed that in the case of a decrease in bolus thickness, HD_ROI and LW_ROI's of the phantom was receiving a higher dose.…”
Section: Discussionmentioning
confidence: 71%
“…For pancreatic cancer, the variable gas volume can highly affect the target coverage in proton or carbon-ion therapy and the beam angle should be optimized [10,11,13]. For (photon) RT, the use of intratumoral markers as the surrogate of the pancreatic tumor in setup verification was found robust against the anatomical changes and gastrointestinal gas [12]. Although bony anatomy-based setup verification was used in the present study, no interfractional tumor position variation was simulated.…”
Section: Discussionmentioning
confidence: 94%
“…There were only a few studies on the dosimetric effect induced by gas changes and its mitigation approach in RT of upper and middle gastrointestinal cancers [10][11][12][13]. For esophageal cancer, the focus was on dosimetric impact of gastric filling [14,15].…”
Section: Introductionmentioning
confidence: 99%